Laser phototherapy induces angiogenesis in the periodontal tissue after delayed tooth replantation in rats - Matos, Felipe-de Souza [UNESP]; Godolphim, Fernanda-de Jesus; Albuquerque-Júnior, Ricardo-Luiz-Cavalcanti; Paranhos, Luiz-Renato; Rode, Sigmar-de Mello [UNESP]; Carvalho, Cláudio-Antonio-Talge [UNESP]; Ribeiro, Maria-Amália-Gonzaga (Medicina Oral, S.L., 2018)
Background: Laser phototherapy (LPT) has been suggested as a new therapeutic tool to improve the repair of replanted teeth. However, its effects and mechanism of action are not yet completely understood. Objectives: This study evaluated histologically the effect of laser phototherapy (LPT) λ808 and λ660 nm on angiogenesis in the periodontal tissue of replanted teeth in rats. Material and Methods: Twenty maxillary right incisors were extracted from twenty Wistar rats and randomly assigned to four groups (n = 5): PN - teeth were stored in paper napkin for 45 min; WM - teeth were immersed in 20 ml of UHT whole cow milk for 45 min; PNL and WML - teeth received the same treatment described for PN and WM, respectively, plus LPT at λ808 and λ660 nm. All root canals were prepared and filled with calcium hydroxide paste. The animals were euthanized 15 days after tooth replantation and angiogenesis was scored by blood vessel counting in the area of periodontal ligament and alveolar bone, using the ImageJ software. Data were analyzed statistically by ANOVA and Tukey's test (α = 5%). Results: LPT at λ808 and λ660 nm caused significant increased angiogenesis on irradiated groups (PNL and WML) when compared to the non-irradiated groups (PN and WM) (p < 0.05). There was no statistically significant difference between PN and WM as well as between PNL and WML (p > 0.05). Conclusions: LPT is capable of stimulating angiogenesis in vivo in the periodontal tissue of replanted teeth.
Keywords: Angiogenesis; Lasers; Tooth avulsion; Tooth replantation; Wound healing